(untitled) (Bangladesh Liver Journal, 2009)
Background: Although chronic hepatitis B virus infection is relatively common in Egypt, the incidental discovery of asymptomatic forms have not been well studied. Aim: To characterize the clinical, serological and histological liver damage among incidentally detected asymptomatic hepatitis B surface antigen (HBsAg)-positive subjects (IDAHS) in Egypt. Methods:We prospectively studied 70 consecutive IDAHS patients. Tests for liver function, serological markers for HBV, HCV, HDV and schistosomiasis were performed for all patients. HBV DNA was determined by the branched DNA technique and PCR. Liver biopsy specimens from 44 patients were studied and scored for activity and fibrosis stage by modified Knodell score and the METAVIR score. HBsAg and HBcAg were immunohistochemically evaluated in the liver tissue. Results: Of the studied 70 patients, 57 (81.6%) were HBeAg-negative and 13 (18.4%) were HBeAg-positive. Hepatic transaminases in HBeAg-positive patients were significantly elevated when compared to HBeAg-negative patients. HBV DNA was detected in only 3% of patients by the b-DNA technique and in 97% by PCR. Pathological examination of liver tissue revealed mild activity in 21 (47.7%) patients. Additionally, 21 patients (47.7%) revealed mild to moderate expansion of portal areas by fibrosis while 7 patients (15.9%) of them showed bridging fibrosis. None of the patients were cirrhotic. Conclusion: The majority of IDAHS subjects are HBeAg negative without elevation of hepatic transaminases. However, they should be considered as patients since viremia is detected in almost all cases using PCR technique, and histopathological evidence of chronic hepatitis B virus infection is present in varying degrees. Key words: Asymptomatic hepatitis B, histopathology, Modified Knodell, METAVIR. doi: 10.3329/blj.v1i1.2621 Bangladesh Liver Journal Vol.1(1) 2009 p20-27